The illusions of special economic zones in developed countries - Augustyński, Iwo (Iluzje skuteczności specjalnych stref ekonomicznych w krajach rozwiniętych, 2019)
One thing missing from most studies on the effects of targeted benefits of Special Economic Zones (SEZs) is a consideration of the indirect and unintended economic effects of these policies. The contribution of this paper is a clarification of this point providing a better identification of opportunity costs of the targeted benefits in SEZs. The author challenges the four most important and interdependent assumptions about the effectiveness of: fiscal incentives, localization, job creation and the negligible distortion of competition. Based on the literature review and data from the Polish SEZs, the author concludes that job creation in the domestic economy due to establishing SEZs is much smaller if the estimates include the negative effects of lower public spending on labour policy caused by fiscal incentives in SEZs, as well as additional unemployment created by distorted competition and the misallocation of resources. Confidence in the evaluation results of SEZs could be increased by efforts to improve the match between the treatment and control data, including the geography and timing of the zone interventions
Biblioteka Regionalisty, 2019, Nr 19, s. 7-19
Keywords: Dolny Śląsk